2020
DOI: 10.1186/s12943-020-01186-6
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs identified in prostate cancer: Correlative studies on response to ionizing radiation

Abstract: As the most frequently diagnosed non-skin cancer in men and a leading cause of cancer-related death, understanding the molecular mechanisms that drive treatment resistance in prostate cancer poses a significant clinical need. Radiotherapy is one of the most widely used treatments for prostate cancer, along with surgery, hormone therapy, and chemotherapy. However, inherent radioresistance of tumor cells can reduce local control and ultimately lead to poor patient outcomes, such as recurrence, metastasis and dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 191 publications
(249 reference statements)
0
23
0
1
Order By: Relevance
“…Alterations in miRNAs/lncRNAs are associated with prostate cancer [ 413 , 414 ]. As the mechanisms behind taxane resistance in CRPC become more defined, the roles of both miRNAs and lncRNAs are emerging [ 305 , 415 , 416 , 417 , 418 ].…”
Section: Taxane Resistance In Prostate Cancermentioning
confidence: 99%
“…Alterations in miRNAs/lncRNAs are associated with prostate cancer [ 413 , 414 ]. As the mechanisms behind taxane resistance in CRPC become more defined, the roles of both miRNAs and lncRNAs are emerging [ 305 , 415 , 416 , 417 , 418 ].…”
Section: Taxane Resistance In Prostate Cancermentioning
confidence: 99%
“…Moreover, a considerable number of studies have demonstrated the dysregulation of multiple miRNAs in PCa, which suggests the use of miRNAs as potential biomarkers for the prediction and prognosis of the disease 4 . In addition, the expression of multiple miRNAs can be altered by radiation in PCa cells and surrounding cells, which are exposed in radiation treatment 6 , 7 . So far, several factors have been documented to be involved in the mutual effects between radiation and miRNAs: first, miRNAs could perform an inhibition role in DNA damage repair induced by radiotherapy 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Several miRNAs have also been reported to exhibit upregulated expressions after radiation so as to modulate the cell cycle progression 9 , 10 . During cell death induced by radiation, miRNAs could provoke cell cycle arrest and increase the radioresistance; furthermore, miRNAs can also regulate epithelial-mesenchymal transition (EMT) 11 , which is often affected by radiation 7 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Ionizing radiation produces free radicals, which results in DNA damage and subsequently halts the fast proliferation of prostate cancer cells. Permanent cell cycle arrest or cell death will occur if DNA repair is not successful [21,22]. Though highly efficient, there are several issues with radiotherapy.…”
Section: Prostate Cancer and Current Therapiesmentioning
confidence: 99%